2020
DOI: 10.1101/2020.05.29.123265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent cancer etiologies drive distinct B cell signatures and tertiary lymphoid structures

Abstract: 26Current immunotherapy paradigms aim to reinvigorate CD8+ T cells, but the contribution 27 of humoral immunity to antitumor immunity remains understudied1,2. Head and neck 28 squamous cell carcinoma (HNSCC) is caused by either human papillomavirus (HPV+) or 29 environmental carcinogens (i.e. tobacco and alcohol; HPV-)3,4. Here, we demonstrate that 30 HPV+ HNSCC patients have transcriptional signatures of germinal center (GC) tumor 31 infiltrating B cells (TIL-Bs) and spatial organization of immune cells consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…We found tumor-infiltrating TFH cells and GC B cells in our analyses of human LUAD and our autochthonous KP model. The former is in line with the observations that NSCLC and other cancer types contain tumor-associated TFH-like cells with an enrichment of a TFH signature (i.e., PDCD1, ICOS, CD200, MAF and IL21) (Bindea et al, 2013;Cillo et al, 2020;Gu-Trantien et al, 2013;Gu-Trantien et al, 2017;Guo et al, 2018;Li et al, 2019;Satpathy et al, 2019;Thommen et al, 2018). In human studies including autoimmune diseases, TFH-like cells have been shown to express CXCL13, the ligand of CXCR5, which was associated with CXCR5 + B cell infiltration and tertiary lymphoid structure (TLS) formation (Bocharnikov et al, 2019;Li et al, 2015;Manzo et al, 2008;Morita et al, 2011;Rao et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…We found tumor-infiltrating TFH cells and GC B cells in our analyses of human LUAD and our autochthonous KP model. The former is in line with the observations that NSCLC and other cancer types contain tumor-associated TFH-like cells with an enrichment of a TFH signature (i.e., PDCD1, ICOS, CD200, MAF and IL21) (Bindea et al, 2013;Cillo et al, 2020;Gu-Trantien et al, 2013;Gu-Trantien et al, 2017;Guo et al, 2018;Li et al, 2019;Satpathy et al, 2019;Thommen et al, 2018). In human studies including autoimmune diseases, TFH-like cells have been shown to express CXCL13, the ligand of CXCR5, which was associated with CXCR5 + B cell infiltration and tertiary lymphoid structure (TLS) formation (Bocharnikov et al, 2019;Li et al, 2015;Manzo et al, 2008;Morita et al, 2011;Rao et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…To examine whether GC B cells and TFH cells associate with clinical outcomes of LUAD patients, we established gene expression signatures for GC B cells and TFH cells based on previous human studies in lymphoid tissues and cancers (Cabrita et al, 2020;Cillo et al, 2020;Milpied et al, 2018;Vella et al, 2019), and refined them based on the data in Figures 1D -1E to reflect the gene expression of GC B cells and TFH cells in LUAD. Analysis of 478 LUAD cases from TCGA showed significant correlations between prolonged overall survival in LUAD patients and GC B cell-or TFH-signatures ( Figure 1F and 1G, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations